Analysis of discrepancies between D1S and R2S results of 2016 DD JET Campaign. (1st September 2022) - Alguacil, J.; Catalan, J.P.; Sauvan, P.; Villari, R.; Batistoni, P.; Sanz, J.
Abstract: In the frame of the WPJET3-DT Technology project within the EUROfusion Consortium program, neutronics experiments are being carried out in preparation for the current deuterium–tritium campaign on JET (DTE2). The experiments are conducted to validate the neutronics codes and tools used in ITER, thus reducing the related uncertainties and the associated risks in the machine operation. Recently, the shutdown dose rate (SDR) results of the 2016 DD campaign have been analyzed using the D1S and R2S computational methodologies showing relevant differences between the results provided by both methods. The greatest discrepancies, found in the SDR calculated in the second octant at 6 h after shutdown, are a factor 2 of difference in the total decay photon flux and a different peak location close to 0.511 MeV. This article presents a detailed analysis of the D1S and R2S simulations performed to find the causes of these discrepancies. The conclusions of the analysis determine that the use of the typical neutron and gamma energy structures used in common R2S simulations can tend to a photon flux significant overestimation or a shift in the output spectrum, respectively. In addition to alerting about this important problem in R2S calculations, this article also proposes a solution to mitigate each effect that can be implemented in R2S codes. The application of the proposed solutions significantly reduces the differences between the photon spectrum calculated with D1S and R2S methods.